Carbon Nanotubes: A Summary of Beneficial and Dangerous Aspects of an Increasingly Popular Group of Nanomaterials - Zhang, Chengke; Wu, Licun; de Perrot, Marc; Zhao, Xiaogang (Frontiers in Oncology, 2021)
Carbon nanotubes (CNTs) are nanomaterials with broad applications and are produced on a large scale. Animal experiments have shown that exposure to CNTs, especially one type of multi-walled carbon nanotube, MWCNT-7, can lead to malignant transformation. CNTs have similar characteristics as asbestos (size, shape, and biopersistence) and use the same molecular mechanisms and signaling pathways as involved in asbestos tumorigenesis. Here, a comprehensive review of the characteristics of carbon nanotubes is provided as well as insights that may assist in the design and production of safer nanomaterials to limit the hazards of currently-used CNTs .